Recent Developments in CE-MS Based Metabolomics - Çelebier, Mustafa; Nenni, Merve (Current Analytical Chemistry, 2021)
Background: Metabolomics has gained importance in clinical applications over the last decade. Metabolomics studies are significant because the systemic metabolome is directly affected by disease conditions. Metabolome-based biomarkers are actively being developed for early diagnosis and to indicate the stage of specific diseases. Additionally, understanding the effect of an intervention on a living organism at the molecular level is a crucial strategy for understanding novel or unexpected biological processes. Results: The simultaneous improvements in advanced analytical techniques, sample preparation techniques, computer technology, and databank contents have enabled more valuable scientific information to be gained from metabolomics than ever before. With over 15,000 known endogenous metabolites, there is no single analytical technique capable of analyzing the whole metabolome. However, capillary electrophoresis-mass spectrometry (CE-MS) is a unique technique used to analyze an important portion of metabolites not accessible by liquid chromatography or gas chromatography techniques. The analytical capability of CE, combined with recent sample preparation techniques focused on extracting polar-ionic compounds, makes CE-MS a perfect technique for metabolomic studies. Conclusion: Here, previous reviews of CE-MS based metabolomics are evaluated to highlight recent improvements in this technique. Specifically, we review papers from the last two years (2018 and 2019) on CE-MS based metabolomics. The current situation and the challenges faced by metabolomic studies are discussed to reveal the high potential of CE-MS.
Keywords: Biomarkers